Achieving Clinical Success in Lingual Orthodontics - Harfin, Julia; Ureña, Augusto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is designed to meet the needs of all orthodontists interested in treating children, adolescents, and/or adults with brackets placed on the palatal and lingual surfaces of the teeth. It explains how to achieve excellent results, comparable to those obtained with labial brackets, by means of techniques performed entirely within the dental office and avoiding use of expensive outside laboratories. The book is divided into three parts. The first is devoted to biomechanics, considering each type of malocclusion and describing how to prepare the arches optimally. This is not a theoretical section; rather it covers aspects acknowledged to be of prime practical importance by students and doctors. The second part explains how to treat the most common malocclusions, with step-by-step descriptions of techniques used in everyday clinical practice. The concluding part of the book describes finishing procedures to enhance aesthetics and discusses long-term results.
BIOMECHANICS: Patient Preparation -- Initial arches to align and level the occlusal plane -- Rotated teeth -- Extraction spaces -- Anchorage control -- Rational use of elastics -- Ideal final arches. CLINICAL APPLICATIONS: Correction of the lower anterior crowding -- Correction of Class II in adult patients -- Normalization of the deep-bite -- The best protocol to extraction cases -- Lingual orthodontics in children. FINISHING IN LINGUAL ORTHODONTICS: Finishing procedures: how to enhance esthetics -- Long term  results -- Summary and outlook.
Keywords: Dentistry; Dentistry